Handbook of historical sociology - Delanty, Gerard; Isin, Engin F. (Engin Fahri) (Sage Publications, 2003)
This Handbook consists of 26 chapters on historical sociology. Part One is devoted to Foundations, Part Two moves on to consider major approaches and Part Three is devoted to the major themes in historical sociology. Systematic and informative it offers readers the most complete and authoritative guide to historical sociology.